RESEARCH COMPONENT AND DISTRIBUTION OF SPECIES Amorphophallus spp. WITH TUBERS CONTAINING GLUCOMANNAN IN THE NORTHERN MOUNTAIN PROVINCES OF VIETNAM - Van Tien, Tran; Van Huan, Ha; Minh Quang, Nguyen; Van Du, Nguyen (Journal of Forestry Science and Technology, 2017)
In Vietnam, recent findings have recorded 25 species of the genus Amorphophallus. Despite some initial results of the contents of Amorphophallus spp. In Vietnam, th ose r esults only record the presence of species in Vietnam territory. In order to pick species with high-glucomannan content, potential to develop in Vietnam, there must be deeper research on species composition, the distrubution in areas, also ecological conditions, developing potential of Amorphophallus spp to become the resources of tuber used for Amorphophallus spp flour manufacturing. This research shows that 6 species with gluconmannan were recorded in 14 mountainous provinces in Northern Vietnam. The Konjac of Amorphophallus spp has the highest gluconmannan content (44.97% in tuber) and has m ost outstanding potential to grow as an industrial crop. In details, 3 years since planted, its mother tuber may reach 600 - 1000 g, including 44 - 47% gluconmannan and produce 5 - 6 tubers a year.